Cracked carbon coated lithium iron phosphate composite material and preparation method thereof

By introducing cyclohexane organic solvents on the surface of lithium iron phosphate using a ball milling process and undergoing plasma treatment, a high-quality carbon cladding layer is formed, which solves the problems of uneven carbon cladding and poor quality in the prior art, and significantly improves the ratio and low-temperature performance of lithium iron phosphate.

CN119920886APending Publication Date: 2025-05-02SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202510122111.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, the carbon-coated lithium iron phosphate modification method has problems such as poor dispersion, uneven and incomplete coating, and poor quality of the carbon-coated layer.

Method used

The ball milling process is used to introduce cyclohexane organic solvent during the ball milling process, and it is evaporated to gaseous state by vacuum treatment, and converted into plasma under discharge conditions. The plasma carbon components are cracked in situ to carbon, forming a complete carbon coating layer on the surface of lithium iron phosphate particles, and the quality of the carbon coating layer is further improved through heat treatment.

Benefits of technology

The uniformity and integrity of the carbon layer on the surface of lithium iron phosphate are achieved, the ionic conductivity and electronic conductivity of the material are improved, and the rate performance and low-temperature cycling performance of lithium iron phosphate are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920886A_ABST
    Figure CN119920886A_ABST
Patent Text Reader

Abstract

The invention provides a cracked carbon coated lithium iron phosphate composite material and a preparation method thereof, and belongs to the technical field of lithium ion batteries. Commercial lithium iron phosphate and a proper amount of cyclohexane organic solvent are mixed and then subjected to cold field plasma assisted ball milling and heat treatment, and cracked carbon coated lithium iron phosphate is obtained. According to the method, commercial lithium iron phosphate is adopted as a raw material, the mechanical effect of ball milling is combined, cyclohexane plasma is utilized, a cracking graphitization carbon layer is constructed on the surface of the lithium iron phosphate, and more complete carbon layer coating on the surface of the lithium iron phosphate is achieved. The obtained cracked carbon coated lithium iron phosphate composite material is subjected to 10C charge-discharge cycle at 30 DEG C, the initial discharge specific capacity reaches 113.2 mAh / g, the capacity retention rate reaches 92.5% after 500 cycles at 10C, and the high-rate cycle stability is good; and when 0.5 C charge-discharge cycle is carried out at-10 DEG C, the initial discharge specific capacity reaches 80mAh / g, the capacity is almost unchanged after 200 cycles at 0.5 C, and good low-temperature cycle performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a cracked carbon-coated lithium iron phosphate composite material and a preparation method thereof. Background Art

[0002] Lithium iron phosphate cathode materials have become a viable option in the market due to their advantages of good safety, low cost and long cycle life, but there are still some problems that restrict the development of lithium iron phosphate cathode materials. In the olivine structure of lithium iron phosphate, electrons can only be transferred along the chain and cannot form a network structure. At the same time, due to the dense arrangement of atoms, the space for lithium ions to move freely is very small and can only diffuse in one-dimensional direction, which makes lithium iron phosphate have the disadvantages of low intrinsic electronic conductivity and low intrinsic ionic conductivity.

[0003] The inherent low electronic conductivity and low ionic conductivity of lithium iron phosphate affect its low temperature performance and rate performance. There are many modification schemes to address these problems, mainly including surface coating, nano-processing and element doping, among which surface carbon coating is the most common modification method. By coating the surface of lithium iron phosphate with carbon materials with excellent conductive properties, the conductivity and ion mobility of the material surface can be improved, and the conductivity between particles can be enhanced. At the same time, the growth of particles can be restricted to a certain extent, thereby controlling the particle size and shortening the movement path of lithium ions. It can effectively improve the rate performance and low temperature performance of lithium iron phosphate, and at the same time enhance the reversibility of the material's lithium ion insertion and extraction, thereby improving the material's specific capacity and cycle performance.

[0004] Currently, the most common modification method for carbon-coated lithium iron phosphate is planetary ball milling solid-phase carbon coating, which has problems such as poor dispersion, uneven and incomplete coating, and poor quality of the carbon coating layer. Summary of the invention

[0005] The purpose of the present invention is to provide a cracked carbon-coated lithium iron phosphate composite material and a preparation method thereof, so as to solve the technical problems of poor dispersibility, uneven and incomplete coating, and poor quality of the carbon coating layer existing in the carbon-coated lithium iron phosphate modification method in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a cracked carbon-coated lithium iron phosphate composite material, comprising the following steps:

[0008] Step 1), mixing lithium iron phosphate and an organic solvent, ball milling and plasma treatment to obtain a mixture;

[0009] Step 2), heat-treating the obtained mixture to obtain a cracked carbon-coated lithium iron phosphate composite material;

[0010] In step 1), during the ball milling process, the organic solvent is in a gaseous state.

[0011] Furthermore, in step 1), the organic solvent includes cyclohexane.

[0012] Furthermore, in step 1), the usage ratio of the lithium iron phosphate and the organic solvent is 1.5 g: 1-1.5 mL.

[0013] Furthermore, in step 1), the ball-to-material ratio of the ball milling is 5 to 10:1;

[0014] The ball milling medium is stainless steel beads, and the diameter of the stainless steel beads is 2 to 5 mm.

[0015] Furthermore, in step 1), the rotation speed of the ball mill is 900-1000 rpm, and the ball milling time is 30-60 min;

[0016] The working system of the ball mill is to mill for 3 to 7 minutes and then stop for 3 to 7 minutes, and then repeat the process until the ball milling time is reached.

[0017] Furthermore, in step 1), the ball milling is performed under a vacuum atmosphere in which the solvent is volatilized.

[0018] Furthermore, in step 1), the discharge current of the plasma treatment is 2 to 4A.

[0019] Furthermore, in step 2), the heat treatment temperature is 600-700° C., and the heat treatment time is 5-6 hours.

[0020] Furthermore, in step 2), the heat treatment atmosphere is a hydrogen-argon mixed gas, wherein the volume proportion of hydrogen is 3-7%.

[0021] The present invention also provides a cracked carbon-coated lithium iron phosphate composite material prepared by the above-mentioned preparation method.

[0022] Beneficial effects of the present invention:

[0023] The cracked carbon coating process of the present invention is different from the traditional physical mixing and in-situ reduction process. The present invention adopts a ball milling process, and introduces an organic solvent containing carbon elements such as cyclohexane during the ball milling process, which is volatilized into a gaseous state by vacuum treatment, and converted into plasma under discharge conditions. The plasma carbon component is cracked into carbon in situ, and a coated carbon layer is formed on the surface of the lithium iron phosphate particles under the mixing action of ball milling, so that the carbon layer of the surface of the lithium iron phosphate that was originally coated incompletely and unevenly is more complete under the coating of the cracked carbon. In addition, the subsequent heat treatment reduces the defects of the lithium iron phosphate, and at the same time, the carbon layer with incomplete carbonization on the surface of the lithium iron phosphate is further carbonized, so that the cracked carbon-coated lithium iron phosphate with high rate and excellent low-temperature cycle performance is obtained, and the carbon content added by the cracking and carbonization of the gaseous carbon source is relatively small, and the carbon itself does not have capacity, which is beneficial to the improvement of the energy density of the lithium iron phosphate. The cracked carbon-coated lithium iron phosphate composite material was subjected to a 10C charge and discharge cycle at 30°C, and the initial discharge specific capacity reached 113.2mAh / g, and the capacity retention rate reached 92.5% after 500 cycles at 10C; when subjected to a 0.5C charge and discharge cycle at -10°C, the initial discharge specific capacity reached 80mAh / g, and the capacity remained almost unchanged after 200 cycles at 0.5C.

[0024] At present, most of the graphene coating of lithium iron phosphate on the market adopts wet process, which has complicated procedures. The preparation method of the present invention only adopts simple plasma-assisted ball milling plus short-time heat treatment to achieve the tight coating of graphene on lithium iron phosphate. The preparation process does not require cumbersome steps such as solvent treatment, hydrothermal reaction, multiple washing or other reprocessing. The process is safe and controllable, the conditions are mild, and it is easy to scale up. Therefore, the carbon-lithium iron phosphate composite material of the present invention and the preparation method thereof have commercial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a TEM image of the cracked and coated lithium iron phosphate composite material obtained in Example 1;

[0026] Figure 2 for Figure 1 A partial enlarged view of

[0027] Figure 3 This is the TEM image of the lithium iron phosphate material in Comparative Example 1;

[0028] Figure 4 for Figure 3 A partial enlarged view of

[0029] Figure 5 The 10C cycle curves of the materials obtained in Examples 1 to 2 and Comparative Examples 1 to 2 at 30°C are shown;

[0030] Figure 6The test curves of the materials obtained in Example 1 and Comparative Example 1 at 30°C and at the rates of 0.1C, 0.5C, 1C, 2C, 5C, 10C, and 0.1C, respectively;

[0031] Figure 7 The cycle curves of the materials obtained in Example 1 and Comparative Example 1 at -10°C and 0.5C respectively;

[0032] Figure 8 This is a SEM image of the lithium iron phosphate material of Comparative Example 1;

[0033] Fig. 9 This is a SEM image of the cracked carbon-coated lithium iron phosphate composite material of Comparative Example 3;

[0034] Fig.10 This is a SEM image of the cracked carbon-coated lithium iron phosphate composite material of Example 1. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a cracked carbon-coated lithium iron phosphate composite material, comprising the following steps:

[0036] Step 1), mixing lithium iron phosphate and an organic solvent, ball milling and plasma treatment to obtain a mixture;

[0037] Step 2), heat-treating the obtained mixture to obtain a cracked carbon-coated lithium iron phosphate composite material;

[0038] In step 1), during the ball milling process, the organic solvent is in a gaseous state.

[0039] In the present invention, in step 1), the ball milling adopts a plasma ball mill.

[0040] In the present invention, in step 1), the lithium iron phosphate is preferably commercial lithium iron phosphate.

[0041] In the present invention, in step 1), the organic solvent comprises cyclohexane, preferably cyclohexane.

[0042] In the present invention, in step 1), the usage ratio of the lithium iron phosphate and the organic solvent is 1.5 g: 1-1.5 mL, preferably 1.5 g: 1.3 mL.

[0043] In the present invention, in step 1), the ball-to-material ratio of the ball milling is 5 to 10:1, preferably 6 to 8:1, and more preferably 7:1;

[0044] The ball milling medium is stainless steel beads, and the diameter of the stainless steel beads is 2 to 5 mm, preferably 3 mm.

[0045] In the present invention, in step 1), the rotation speed of the ball mill is 900-1000 rpm, preferably 950 rpm; the ball milling time is 30-60 min, preferably 40-50 min, and more preferably 45 min;

[0046] The working system of the ball mill is to mill for 3 to 7 minutes and then stop for 3 to 7 minutes, preferably, to mill for 5 minutes and then stop for 5 minutes, and the cycle is repeated until the ball milling time is reached.

[0047] In the present invention, in step 1), the ball milling is performed under a vacuum atmosphere in which the solvent is volatilized.

[0048] In the present invention, in step 1), the discharge current of the plasma treatment is 2-4A, preferably 3A.

[0049] In the present invention, in step 2), the heat treatment temperature is 600-700°C, preferably 620-680°C, and more preferably 650°C; the heat treatment time is 5-6h, and preferably 5.5h.

[0050] In the present invention, in step 2), the atmosphere of the heat treatment is a hydrogen-argon mixed gas, wherein the volume proportion of hydrogen is 3-7%, preferably 5%.

[0051] The present invention also provides a cracked carbon-coated lithium iron phosphate composite material prepared by the above-mentioned preparation method.

[0052] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0053] Example 1

[0054] Take 1.5g of lithium iron phosphate and 1mL of cyclohexane and add them into a plasma ball mill, and then add a stainless steel ball with a diameter of 2mm according to a ball-to-material ratio of 10:1. After sealing the ball mill, evacuate the vacuum, and then place the ball mill on a plasma ball mill. Ball milling is carried out at a ball milling speed of 960rpm and a discharge current of 3A. The process of ball milling for 5min and stopping for 5min is repeated 12 times, for a total of 60min of ball milling. The ball milling product is calcined at 600℃ for 5h in a hydrogen-argon mixed gas atmosphere (hydrogen accounts for 5% by volume) to obtain a cracked carbon-coated lithium iron phosphate composite material.

[0055] Example 2

[0056] Take 1.5g of lithium iron phosphate and 1.5mL of cyclohexane and add them to a plasma ball mill, and then add a stainless steel ball with a diameter of 2mm according to a ball-to-material ratio of 10:1. After sealing the ball mill, evacuate the vacuum, and then place the ball mill on a plasma ball mill. Ball milling is carried out at a ball milling speed of 960rpm and a discharge current of 3A. The process of ball milling for 5min and stopping for 5min is repeated 12 times, for a total of 60min of ball milling. The ball milling product is calcined at 600℃ for 5h in a hydrogen-argon mixed gas atmosphere (hydrogen accounts for 5% by volume) to obtain a cracked carbon-coated lithium iron phosphate composite material.

[0057] Example 3

[0058] Take 1.5g of lithium iron phosphate and 1mL of cyclohexane and add them into a plasma ball mill, and then add a stainless steel ball with a diameter of 5mm according to a ball-to-material ratio of 5:1. After sealing the ball mill, evacuate the vacuum, and then place the ball mill on a plasma ball mill. Ball milling is carried out at a ball milling speed of 960rpm and a discharge current of 3A. The process of ball milling for 5min and stopping for 5min is repeated 12 times for a total of 60min of ball milling. The ball milling product is calcined at 600℃ for 5h in a hydrogen-argon mixed gas atmosphere (hydrogen accounts for 5% by volume) to obtain a cracked carbon-coated lithium iron phosphate composite material.

[0059] Comparative Example 1

[0060] Different from Example 1, in this comparative example, commercial lithium iron phosphate that has not been modified by plasma ball milling and carbon coating is selected as the positive electrode material.

[0061] Comparative Example 2

[0062] Different from Example 1, in this comparative example, the organic solvent is benzene.

[0063] Comparative Example 3

[0064] Different from Example 1, in this comparative example, the heat treatment step of the ball-milled product was omitted.

[0065] Performance Testing

[0066] The positive electrode material of lithium iron phosphate, conductive carbon (C45) and binder polyvinylidene fluoride (PVDF) containing N-methyl-2-pyrrolidone (NMP) were mixed in a mass ratio of 8:1:1, stirred in a degassing machine for 40 minutes to obtain a positive electrode slurry, and the positive electrode slurry was evenly coated on one side of a clean aluminum foil, placed in a vacuum drying oven at 80°C for vacuum drying for 12 hours, and the electrode was taken out and cut into a disc with a diameter of 12 mm. In a glove box with a moisture and oxygen content of less than 10 ppm and filled with argon, the positive electrode in (2) was used, a lithium sheet was used as a negative electrode, an electrolyte of 1 mol / L LiPF6 (solvent is EC:DEC=1:2Vol%, and 10% FEC was added), and a PP / PE / PP composite separator with a thickness of 25 μm was used to assemble a CR2025 button cell. The capacity test was carried out in the LAND CT2001A battery testing system, and the charge and discharge experimental conditions were as follows: 30℃ activation was performed by charging to 4.0V at a constant current of 0.1C and then discharging to 2.5V at a constant current for 3 cycles, and then 500 cycles of 30℃ cycle performance test were performed by charging to 4.0V at a constant current of 10C and then discharging to 2.5V at a constant current; 30℃ rate performance test was performed by charging to 4.0V at a constant current of 0.1C, 0.5C, 1C, 2C, 5C, 10C, and 0.1C respectively and then discharging to 2.5V at a constant current for 5 cycles.

[0067] Table 1 shows the performance test results of the positive electrode materials obtained in Examples 1 to 2 and Comparative Examples 1 to 2

[0068]

[0069] The carbon and sulfur analyzer was used to analyze the carbon and sulfur of the materials obtained in Comparative Example 1 and Example 1, respectively, and the carbon content of the two materials was quantitatively analyzed. The results showed that the carbon content of Comparative Example 1 was 1.17wt.%, and the carbon content of Example 1 was 1.27wt.%, which shows that new carbon was indeed introduced into the material through the preparation method of the present invention.

[0070] It can be seen from the above embodiments that the present invention provides a cracked carbon-coated lithium iron phosphate composite material and a preparation method thereof. Figure 1 , Figure 2 They are respectively a TEM image of the cracked and coated lithium iron phosphate composite material obtained in Example 1 and a local enlarged image thereof, Figure 3 , Figure 4 They are respectively the TEM image of the lithium iron phosphate material in Comparative Example 1 and its local enlarged image. Figure 3 , Figure 4 It can be seen that there are some carbon layers on the surface of commercial lithium iron phosphate, but the carbon layer on the surface is incomplete and uneven. Figure 1 and Figure 2It can be seen that plasma ball milling completely covers the surface of lithium iron phosphate with a layer of carbon layer. Compared with Comparative Example 1, the uniformity and integrity of the surface carbon layer coating have been significantly improved. The improvement of the surface carbon layer coating state is beneficial to improving the ionic conductivity and electronic conductivity of the material, thereby improving the charge and discharge performance of lithium iron phosphate, especially the performance at high rates.

[0071] Figure 5 The 10C cycle curves of the materials obtained in Examples 1-2 and Comparative Examples 1-2 at 30°C are shown. Figure 5 As shown, after plasma ball milling combined with heat treatment, the discharge specific capacity of the cracked carbon-coated lithium iron phosphate at a high rate of 10C is higher than that of the commercial lithium iron phosphate that has not been modified. This is because the cracked carbon forms a more complete coating layer on the surface of the lithium iron phosphate, which is beneficial to improve the ionic conductivity and electronic conductivity of the lithium iron phosphate. This shows that the method of preparing cracked carbon-coated lithium iron phosphate by plasma ball milling can effectively improve the high-rate discharge specific capacity of lithium iron phosphate; by comparing the 10C cycle performance curves of Example 1, Example 2 and Comparative Example 2, it can be seen that by the method of plasma ball milling to modify the cracked carbon-coated lithium iron phosphate material, when cyclohexane is selected as the carbon source, the prepared composite material has a better 10C high-rate discharge specific capacity than when benzene is selected as the carbon source. This is because different carbon sources have different structures, resulting in different carbonization effects, which shows that using cyclohexane as the carbon source is a better solution for this method.

[0072] Figure 6 The following are the rate test curves of the materials obtained in Example 1 and Comparative Example 1 at 30°C at 0.1C, 0.5C, 1C, 2C, 5C, 10C, and 0.1C. Figure 6 It can be seen that the cracked carbon-coated lithium iron phosphate has better rate performance than commercial lithium iron phosphate, and has higher discharge specific capacity at each current density. The results are consistent with the cycle performance test results. The higher the rate, the higher the discharge specific capacity of the cracked carbon-coated lithium iron phosphate compared with commercial lithium iron phosphate. This is because new carbon is added during the modification process. The carbon content of the cracked carbon-coated lithium iron phosphate is higher than that of commercial lithium iron phosphate, and the carbon itself does not provide capacity. At lower rates, the discharge specific capacity of lithium iron phosphate itself is higher, so the improvement effect is not obvious. At higher rates, the discharge specific capacity of lithium iron phosphate is lower, and the effect of the ionic conductivity and electronic conductivity improvement brought by the cracked carbon coating becomes obvious, so it has a better modification effect at high rates. The rate performance test results are consistent with the cycle performance test. As evidence, it shows that the preparation of cracked carbon-coated lithium iron phosphate by plasma ball milling can effectively improve the high-rate discharge specific capacity of lithium iron phosphate.

[0073] Figure 7The following are the cycle curves of the materials obtained in Example 1 and Comparative Example 1 at -10°C and 0.5°C respectively. Figure 7 It can be seen that the carbon-coated lithium iron phosphate material prepared by plasma ball milling has better low-temperature performance than commercial lithium iron phosphate. This is because the carbon coating is prepared by plasma ball milling, and the surface of the lithium iron phosphate has a more complete coating layer, which is beneficial to improve the ionic conductivity and electronic conductivity of the lithium iron phosphate, thereby improving the low-temperature cycle performance of the lithium iron phosphate.

[0074] The lithium iron phosphate materials prepared in Comparative Example 1, Comparative Example 3 and Example 1 were characterized by SEM. Figures 8 to 10 As shown. Figure 8 It can be seen that the surface of commercial lithium iron phosphate particles that have not been treated with cracked carbon coating is relatively smooth, and there is no obvious attachment with poor conductivity; Fig. 9 It can be seen that a large number of poorly conductive attachments appear on the surface of the lithium iron phosphate composite material that has been treated with plasma ball milling and carbon coating but not heat treated. This indicates that the carbonization degree of the carbon source on the surface of the lithium iron phosphate material treated only by plasma ball milling is incomplete, and there are organic substances that are not completely carbonized and have poor conductivity. Fig.10 It can be seen that by performing heat treatment at 600°C under a hydrogen-argon mixture, the poorly conductive attachments on the surface of the lithium iron phosphate disappear, the organic matter is further carbonized, and the morphology of the cracked carbon-coated lithium iron phosphate material is not significantly changed compared with the commercial lithium iron phosphate material. This shows that the heat treatment step plays an important role in the present invention. In addition to its own annealing effect, it also plays a role in further carbonizing the organic matter on the surface of the lithium iron phosphate, which is beneficial to the improvement of the electrochemical performance of the lithium iron phosphate.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a cracked carbon-coated lithium iron phosphate composite material, characterized in that: The following steps are involved: Step 1), mixing lithium iron phosphate and an organic solvent, ball milling and plasma treatment to obtain a mixture; Step 2), heat-treating the obtained mixture to obtain a cracked carbon-coated lithium iron phosphate composite material; In step 1), during the ball milling process, the organic solvent is in a gaseous state.

2. The method for preparing a cracked carbon-coated lithium iron phosphate composite material according to claim 1, characterized in that: In step 1), the organic solvent comprises cyclohexane.

3. The method for preparing a cracked carbon-coated lithium iron phosphate composite material according to claim 1 or 2, characterized in that: In step 1), the usage ratio of the lithium iron phosphate and the organic solvent is 1.5 g: 1-1.5 mL.

4. The method for preparing a cracked carbon-coated lithium iron phosphate composite material according to claim 3, characterized in that: In step 1), the ball-to-material ratio of the ball mill is 5 to 10:1; The ball milling medium is stainless steel beads, and the diameter of the stainless steel beads is 2-5 mm.

5. The method for preparing a cracked carbon-coated lithium iron phosphate composite material according to claim 1, 2 or 4, characterized in that: In step 1), the ball milling speed is 900-1000 rpm, and the ball milling time is 30-60 min; The working system of the ball mill is to mill for 3 to 7 minutes and then stop for 3 to 7 minutes, and then repeat the process until the milling time is reached.

6. The method for preparing a cracked carbon-coated lithium iron phosphate composite material according to claim 5, characterized in that: In step 1), the ball milling is performed under a vacuum atmosphere in which the solvent is volatilized.

7. The method for preparing a cracked carbon-coated lithium iron phosphate composite material according to claim 4 or 6, characterized in that: In step 1), the discharge current of the plasma treatment is 2-4A.

8. The method for preparing a cracked carbon-coated lithium iron phosphate composite material according to claim 7, characterized in that: In step 2), the heat treatment temperature is 600-700° C., and the heat treatment time is 5-6 hours.

9. The method for preparing a cracked carbon-coated lithium iron phosphate composite material according to claim 8, characterized in that: In step 2), the heat treatment atmosphere is a hydrogen-argon mixed gas, wherein the volume proportion of hydrogen is 3-7%.

10. The cracked carbon-coated lithium iron phosphate composite material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing lithium iron phosphate serving as cathode material of nano-level lithium ion battery

    CN102522546A

  • Hydrothermal lithium iron phosphate carbon coating method

    CN106207251A

  • Nonmetal oxygen reduction catalyst material as well as preparation method and application thereof

    CN106356538A

  • Lithium ion battery silicon carbon negative electrode material and preparation method thereof

    CN110336024A

  • Preparation method of carbon-coated nickel-cobalt-manganese ternary material, carbon-coated nickel-cobalt-manganese ternary material and lithium ion battery positive electrode material with carbon-coated nickel-cobalt-manganese ternary material

    CN114583125A

Cited By

  • Composite positive electrode material and preparation method thereof

    CN121355211A